Agroclimatic Indices Dataset for Characterizing Crop Water Requirements, Dry and Wet Spells, Heatwaves, and Water Balance in Agricultural Regions of Angola - Barrios Pérez, Camilo; Sotelo Betancurt, Humberto Steven; Ramírez Villegas, Julián Armando (2023)
This database contains spatial information with a 0.05° grid resolution of specific agroclimatic indices for maize, dry beans, soybeans, and coffee regions in Angola. In total, the database comprises 13 agroclimatic indices for each crop, grouped as follows: 1. Dry Conditions Indices: • Number of Dry Days • Number of Dry Spells • Average Length of Dry Spells